DARI SISA MINYAK KE CAHAYA: PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN LILIN RAMAH LINGKUNGAN - Saputra, Annisa Az Zahra Mayang; Amrina, Dania Hellin (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Used cooking oil, which is often disposed of as household waste, can cause negative environmental impacts if not managed properly. To address this issue, a community service program was carried out through training on producing environmentally friendly candles made from used cooking oil for housewives in Karanganyar Hamlet, Mungkung Village, Kalikajar District, Wonosobo Regency. The aim of this program was to raise community awareness of household waste management while providing practical skills that are useful for daily needs and potential small-scale businesses. The method included socialization about the dangers of used oil, demonstrations of candle-making techniques, and direct practice by participants using simple and easily available tools and materials. The results showed that participants successfully produced candles independently and were enthusiastic about replicating the process at home. Some participants even expressed interest in developing this skill into a home-based business. Thus, the program proved effective in empowering the community, reducing environmental pollution, and opening opportunities for improving family income.